The Molecular and Epidemiological Atlas of Primary Orbital Lymphoma: A Global Meta-Analysis of 3,832 Cases and Pathophysiological Correlates - Silvia Roza; Ardizal Rahman; Mardijas Efendi (HM Publisher, 2025)
Background: Primary orbital lymphoma is the most common orbital malignancy in adults, yet its global distribution and the prevalence of its histopathological subtypes remain poorly defined by large-scale evidence. This study provides a comprehensive quantitative synthesis of the global landscape of orbital lymphoma to inform diagnostic frameworks and guide future research. Methods: Following PRISMA guidelines, we conducted a systematic review and meta-analysis of studies published between January 2015 and December 2023. We searched PubMed, Scopus, Web of Science, and Embase for observational studies reporting histopathological data on orbital lymphoma. Two independent reviewers performed study selection, data extraction, and quality appraisal using the Joanna Briggs Institute (JBI) checklist. Pooled prevalence for each lymphoma subtype was calculated using a random-effects model. Heterogeneity was explored via subgroup analyses and meta-regression, and the robustness of findings was confirmed with a sensitivity analysis. Results: Fifteen studies comprising 3,832 patients met the inclusion criteria. Extranodal marginal zone lymphoma (EMZL) was the most prevalent subtype globally, with a pooled prevalence of 57.1% (95% CI: 51.5-62.7%). This was followed by diffuse large B-cell lymphoma (DLBCL) at 16.5% (95% CI: 13.1-20.0%), follicular lymphoma (FL) at 10.2% (95% CI: 8.0-12.4%), mantle cell lymphoma (MCL) at 5.1% (95% CI: 3.6-6.6%), and small lymphocytic lymphoma (SLL) at 3.4% (95% CI: 2.2-4.5%). Subgroup analysis revealed a significantly higher prevalence of EMZL in Asia (61.3%) compared to Europe (54.2%) and North America (55.8%) (p=0.04), while FL was more common in North American (14.1%) and European (12.8%) cohorts versus Asian cohorts (4.5%) (p<0.01). Sensitivity analysis confirmed the stability of these estimates. Conclusion: This meta-analysis establishes EMZL as the predominant histopathological subtype of orbital lymphoma worldwide, while highlighting profound geographical disparities in the distribution of EMZL and FL. These findings provide a robust global benchmark critical for clinical practice and underscore the influence of distinct geographical, genetic, and microenvironmental factors in orbital lymphomagenesis.